2020
DOI: 10.17576/gema-2020-2003-15
|View full text |Cite
|
Sign up to set email alerts
|

‘A Long Battle Ahead’: Malaysian and Singaporean Prime Ministers Employ War Metaphors for COVID-19

Abstract: The short article reports a preliminary exploration about how the Prime Ministers of Malaysia and Singapore frame COVID-19 through metaphors. The framing can shape our understanding of the virus. The Prime Ministers gave public broadcasts on or to the media in March, April and May 2020. The analysis of the broadcasts is comprised of metaphor identification using the Metaphor Identification Procedure (MIP), and metaphor interpretation. COVID-19 in the Prime Ministers' broadcasts is conceptualized by a few metap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 14 publications
0
25
0
2
Order By: Relevance
“…Because the government's ineffective communication during the Covid-19 pandemic can lead to confusion, misunderstanding and bring social impacts on the citizens as well as prolong the pandemic period (Kim & Kreps, 2020). Studies by Eriyanto and Ali (2020) and Olimat (2020b) established that studies on how the government employed discursive strategies to inspire the citizens have not been researched, while Kim and Kreps's study (2020) demonstrated that research on the language used by the government in communication during the Covid-19 pandemic is timely, although studies such as Kim and Kreps (2020) and Rajandran (2020) have been carried out.…”
Section: Introductionmentioning
confidence: 99%
“…Because the government's ineffective communication during the Covid-19 pandemic can lead to confusion, misunderstanding and bring social impacts on the citizens as well as prolong the pandemic period (Kim & Kreps, 2020). Studies by Eriyanto and Ali (2020) and Olimat (2020b) established that studies on how the government employed discursive strategies to inspire the citizens have not been researched, while Kim and Kreps's study (2020) demonstrated that research on the language used by the government in communication during the Covid-19 pandemic is timely, although studies such as Kim and Kreps (2020) and Rajandran (2020) have been carried out.…”
Section: Introductionmentioning
confidence: 99%
“…This is currently being revived by Xi Jinping as part of his rhetorical imagery (Gallelli, 2020); indeed, he officially declared a "people's war" against the virus in the early stages of the outbreak in the Hubei province. Perhaps also as a consequence of this, WAR/CONFLICT metaphors were taken up globally as a leitmotif in public communication about the pandemic (e.g., Grandi & Piovan, Rajandran, 2020;Sabucedo et al, 2020) 12 . At the same time, convergence towards this kind of conceptualization may also have been favored by a tendency to represent disease in terms of war already present in the Western culture, which has been shown by several studies (notably Sontag, 1991), as well as by the parallels that were drawn, as the disease spread worldwide, between the current situation and the Second World War, also in terms of the exceptional measures taken.…”
Section: Framing the Virus: Metaphor Nominalization And Appraisalmentioning
confidence: 99%
“…It is remarkable that COVID-19 is verbalised through war metaphors all over the world: they are registered in public discourse in Italy (Tan et al, 2020), Southeast Asia (Rajandran, 2020), and the United States (Olimat, 2020) (also see (Connolly, 2020)). War rhetoric on the coronavirus pandemic is so globally pervasive that some scholars have urged speakers to stop using it, since metaphorical expressions may lead to distorted mental representations (see, for example, (Arawi et al, 2020;Boyte & Throntveit, 2020;Burke, 2020)).…”
Section: Literature Reviewmentioning
confidence: 99%